2018
DOI: 10.1007/s12551-018-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filaments in cardiomyopathy

Abstract: Intermediate filament (IF) proteins are critical regulators in health and disease. The discovery of hundreds of mutations in IF genes and posttranslational modifications has been linked to a plethora of human diseases, including, among others, cardiomyopathies, muscular dystrophies, progeria, blistering diseases of the epidermis, and neurodegenerative diseases. The major IF proteins that have been linked to cardiomyopathies and heart failure are the muscle-specific cytoskeletal IF protein desmin and the nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 264 publications
4
72
0
16
Order By: Relevance
“…The presence of insoluble tetramers may be explained by an inefficient desmin assembling leading to the collapse and aggregation of filaments [44]. It is well established that IF are dynamic structures and reversible phosphorylation is a mechanism that plausibly maintains this dynamism affecting its assembling and disassembling [48,49]. In line with this, we found that in Drp/ MC mice desmin was hyperphosphorylated in Ser-31 by a hyperactivated Cdk-1.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The presence of insoluble tetramers may be explained by an inefficient desmin assembling leading to the collapse and aggregation of filaments [44]. It is well established that IF are dynamic structures and reversible phosphorylation is a mechanism that plausibly maintains this dynamism affecting its assembling and disassembling [48,49]. In line with this, we found that in Drp/ MC mice desmin was hyperphosphorylated in Ser-31 by a hyperactivated Cdk-1.…”
Section: Discussionsupporting
confidence: 83%
“…Desmin preserves mitochondria in close proximity to myofibrils and promotes the transfer of the energy. It is able to sense and respond to stress regulating many processes including the gene expression, thus desmin can be considered a mechanosensor and transducer of signals to the nucleus [42,48,50]. Moreover, desmin disruption compromises the cross-talk between mitochondria and other organelles affecting mitochondrial biogenesis and function [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations on the LMNA gene are associated with more than 10 clinical pathologies, known as laminopathies, with DCM and skeletal myopathies being among the most common ones which can occur isolated or in association with disorders affecting other tissues [5,12,14]. On the other hand, dysfunctional desmin network due to desmin gene mutations or posttranslational modifications (PTMs) causes a wide range of clinical and pathological manifestations, mainly hallmarked by abnormal desmin positive sarcoplasmic aggregates, which are collectively called desminopathies [2,[15][16][17][18][19]. Importantly, mutations in the small heat shock protein Β-Crystallin (ΒCry) also cause desmin aggregate-related DCM and HF [1,2,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that the changes in DNA methylation that we observed are due to a change in cell‐type composition in the CRS hearts rather than an alteration in DNA methylation in cardiomyocytes (57). However, in the case of desmin and Adra1b , the change in methylation is likely specific to cardiomyocytes and not caused by recruitment of noncardiomyocyte cells such as fibroblasts and endothelial cells, because desmin is a muscle‐specific gene (58) and Adra1b is predominantly expressed in cardiomyocytes (59). Whether altered methylation of desmin or Adra1b , and the consequent change in their expression, is causal of, rather than correlational to, the LV chamber dilatation that we observed in CRS mice is unclear.…”
Section: Discussionmentioning
confidence: 99%